2010
DOI: 10.1007/s00415-010-5455-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels and neuromyelitis optica

Abstract: Uric acid (UA) has been reported to be reduced in the serum of patients with multiple sclerosis (MS) and optic neuritis (ON). However, the relationship between UA and neuromyelitis optica (NMO) was unknown. NMO was claimed to be a distinct nosologic entity from MS. The aim of our study was to investigate the correlation between serum UA level and the clinical characteristics of NMO. The serum UA level was measured in 403 Chinese patients; 69 with NMO, 32 ON, 127 MS, 80 cerebral infarction (CI) patients, and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…However, compared to the healthy subjects, UA levels measured during relapses were significantly lower in both NMO and MS groups ( P < 0.01, both). As there were only three male patients with NMO, and female UA levels are lower in normal subjects , we separately analysed men and women (Table ). During relapses, both MS and NMO female patients had significantly lower UA levels than the female healthy subjects ( P < 0.01, both) and that during stable disease, UA levels of female patients with NMO were not significantly different from those of the female healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared to the healthy subjects, UA levels measured during relapses were significantly lower in both NMO and MS groups ( P < 0.01, both). As there were only three male patients with NMO, and female UA levels are lower in normal subjects , we separately analysed men and women (Table ). During relapses, both MS and NMO female patients had significantly lower UA levels than the female healthy subjects ( P < 0.01, both) and that during stable disease, UA levels of female patients with NMO were not significantly different from those of the female healthy subjects.…”
Section: Resultsmentioning
confidence: 99%
“…This disorder has been suggested as a variant of MS in the past; however, it is now accepted that NMO is different from MS in the context of neurological, immunological, radiological and pathological findings. So far, there have been no studies of UA levels in NMO, except one report which found that serum UA levels of patients with NMO were reduced, but not correlated with magnetic resonance image (MRI) activity, disease disability or duration of disease . We performed a hospital‐based study to investigate a possible association between serum UA levels and disease activity in patients with NMO.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this, uric acid administration has been beneficial in EAE. However, some recent studies failed to correlate uric acid serum levels and several clinical parameters of MS and ON3031. Stroke is also another disease in which uric acid could play a protective role.…”
Section: Discussionmentioning
confidence: 99%
“…Serum oxidative stress markers, including malondialdehyde, advanced oxidation protein products, peroxidation potential, SOD, catalase and total hydroperoxides, were overproduced in patients with NMO [18]. Our earlier study [19] indicated reduced serum UA levels in patients with NMO, no correlation with disease activity and levels of UA, and that serum UA levels between patients with NMO and MS had no statistic difference. However, serum UA in male NMO was slightly higher than those in male MS. Interestingly, in this study, patients with NMO also showed reduced serum UA, bilirubin and albumin, and there were no significant differences in serum UA, Tbil, Ibil and albumin levels between patients with NMO and MS.…”
Section: Discussionmentioning
confidence: 99%